Transient Transfection of the Respiratory Epithelium with Gamma Interferon for Host-Directed Therapy in Pulmonary Tuberculosis - Reena Bharti; Ashish Srivastava; Trisha Roy; Khushboo Verma; D.V. Siva Reddy; Hasham Shafi; Sonia Verma; Sunil K. Raman; Amit K. Singh; Jyotsna Singh; Lipika Ray; Amit Misra (Elsevier, 2020)
Nebulized gamma interferon (IFN-γ) protein has been studied for clinical safety and efficacy against pulmonary tuberculosis (TB). The protein is expensive, requires a cold chain, and is difficult to deploy in limited-resource, high-incidence settings. We generated a preclinical proof of concept (PoC) for a dry powder inhalation (DPI) containing DNA constructs to transiently transfect the lung and airway epithelium of mice with murine IFN-γ. Bacterial colony-forming units (CFU) in the lungs of mice infected with Mycobacterium tuberculosis (Mtb) reduced from about 106/g of tissue to ~104 after four doses given once a week. Nodular inflammatory lesions in the lungs reduced significantly in number. Immunohistochemistry of infected lung sections for LC3-1 and LAMP-1 indicated autophagy induction between 18 and 48 h after inhalation. ELISA on bronchoalveolar lavage (BAL) fluid showed differences in kinetics of IFN-γ concentrations in the epithelial lining fluid of healthy versus infected mice. Uninfected mice receiving DNA constructs expressing a fluorescent protein were live-imaged. The fluorescence signals from the intracellular protein peaked at about 36 h after inhalation and declined by 48 h. These results establish preclinical PoC of the efficacy of a DPI and dosing regimen as a host-directed and transient gene therapy of experimental pulmonary TB in mice, justifying preclinical development.